Demands of physical activities and efforts in elite basketbal - R.A. Ribeiro; L.A. Monezi (Federación Extremeña de Balonmano; University of Extremadura, 2016)
There is a great importance in describing the demands of physical exertion of the players in official games for we can organize better periodization training. The aim of this study is to propose a new form of demand physical exertion rating of basketball players and analyze the five existing positions in the game. The classification was divided into five classes and their subclass, as follows: a displacement class with its subclasses: forward pair back side, stopped and defensive position, the class of power contact with its subclass one against one, box out, pick and faults, the class of jump, upper-body movements and dribble. We analyzed two teams in a game quarter of the New Basketball Brazil, the players were divided by the positions / functions operating in the basketball game. Found difference between the frequencies, medium time and total time in the displacement class and power contact between positions thus we conclude that it is necessary to detail the demands of physical exertion and analyze five separate positions indicating the need individualized training.